Synthesis and characterization of CZTS thin films by spray pyrolysis - Ow, Wen Hui. (2012)
Thin films of Cu2ZnSnS4 (CZTS) that can function as absorber layers in thin film heterojunction solar cells have been deposited using chemical spray pyrolysis technique on glass substrates held at substrate temperatures of 430°C and 500°C. The effect of copper salt concentrations on CZTS films is investigated. It is observed that the grain size of the films increase with copper content in the films, but the formation of CuS is evident when the Cu proportion is greater than 1.7. Films deposited at the higher temperature give much more crystalline films with larger grain size. The optical band-gaps of these samples deposited at higher temperature are more comparable to the theoretical band-gap of CZTS.